The Value Chain Analysis in The Dried Mackerel Meatball Processing Industry - Syamsudin; Gerry Anugrah; Heru Winarno (University of Technology Yogyakarta, 2023)
In facing the level of trade competition, every industry is required to be able to have high competitiveness in order to remain superior, this is no exception on a regional, national and even local industrial scale. PD. Karya Cipta Mandiri is a food processing industry with dried mackerel fish balls as a product. The existence of uncertainty in the company's production that comes from a lack of supply causes a decline in sales and makes the company suffer losses, this is because the company only has relationships with suppliers in only one province, namely Banten. The purpose of this study is to make an in-depth analysis of how the food processing industry for mackerel meatball products manages its activities in its corporate value chain. This is important because through value chain analysis, activities that have and have not added value to a company's competitive advantage can be identified. The analysis used includes analysis of internal conditions carried out in two ways, Resource Analysis and Capability Analysis. The next step is to assess the value chain analysis of the five main activities and four supporting activities. The research results identified two resources and two potential strength capabilities that can be used to help companies determine competitive advantage strategies, while it is known that five strategically relevant potential disadvantages have been identified to become sources of long-term competitive advantage strategies in companies, and it is explained that maintaining ties that can generate profits from the company with suppliers is essential for the company